PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN PEMECAHAN MASALAH FISIKA SISWA PADA MATERI GAYA DAN HUKUM NEWTON DI SMP NEGERI 1 PEGAJAHAN T.A 2015/2016 - Dahlia, Dahlia; Sahyar, Sahyar (JURNAL IKATAN ALUMNI FISIKA UNIVERSITAS NEGERI MEDAN, 2017)
This study aims to investigate the effect of problem-based learning (PBL) model on studentâs problem-solving skills in force and Newtonâs law subject matter atÂ  class VIII SMP N.1 Pegajahan A.Y 2015/2016. This research was a quasi experimental with population eight grade students, which consisted six classes and the sample consisted two classes: class VIII-5 used problem-based learning (PBL) model and VIII-2 used conventional learning, each class consist 33 students. Instruments was essay test form with number about 10 items. The gain value of problem-solving skills in experimental class used problem-based learning model was 0.41 included in the moderate category, and class used conventional learning was 0.28 included in the low category. Proved from hypothesis test, problem-solving skills applied problem-based learning model was better than conventional learning in class VIII semester II at SMP in force and Newtonâs law subject matter.